2015
DOI: 10.1021/acs.orglett.5b01844
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Amphirionin-4

Abstract: The first total synthesis of amphirionin-4 has been achieved using a combination of cross-coupling strategies to access the polyene side chain and a chlorohydrin-based approach to construct the tetrahydrofuranol core. The remote C9-stereocenter was introduced through a Nozaki-Hiyama-Kishi coupling that proceeded with remote stereoinduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…495) and ciguatoxin 54-deoxyCTX1B 496 have been achieved. 497,498 Polyketide synthesis genes unique to two Gambierdiscus species that produce maitotoxin 499 were characterised, perhaps implicating them in the biosynthesis of this metabolite. 500 Studies with Karenia brevis showed that brevetoxin 501 is localised in the chloroplasts and interacts with light harvesting complex II (LHCII) and thioredoxin, so is likely implicated in nonphotochemical quenching (NPQ).…”
Section: Dinoagellatesmentioning
confidence: 99%
“…495) and ciguatoxin 54-deoxyCTX1B 496 have been achieved. 497,498 Polyketide synthesis genes unique to two Gambierdiscus species that produce maitotoxin 499 were characterised, perhaps implicating them in the biosynthesis of this metabolite. 500 Studies with Karenia brevis showed that brevetoxin 501 is localised in the chloroplasts and interacts with light harvesting complex II (LHCII) and thioredoxin, so is likely implicated in nonphotochemical quenching (NPQ).…”
Section: Dinoagellatesmentioning
confidence: 99%
“…NHK coupling 16,17 between aldehyde 4 and vinyl iodide 22 in DMF at 0 °C to 23 °C for 24 h provided TBS protected amphirionin-4 as a major diastereomer in 60 % yield. The diastereoselectivity of this reaction was increased to (4:1) 13 in favor of the desired isomer 41 through strong 1,4-stereoinduction. Deprotection of the TBS-group with 70% HF, 30% pyridine in the presence of excess pyridine furnished (−)-amphirionin-4 ( 1 ) in excellent yield.…”
Section: Resultsmentioning
confidence: 98%
“…A similar strategy was also utilized by Britton and co-workers. 13 We planned to synthesize the vinyl iodide 3 from the corresponding allyl derivative through a Lewis acid catalyzed allylation of an oxocarbenium ion generated from α–hydroxy lactone 5 . This optically active lactone 5 could be readily obtained by the ozonolysis and subsequent reduction of commercially available α-methylene-γ-valerolactone 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of (+)-amphirionin-4 was elucidated by Tsuda and co-workers using extensive NMR analysis and the absolute configuration of the C4 and C8 hydroxyl groups was determined by Mosher ester analysis . Recently, Britton and co-workers have reported the first synthesis of amphirionin-4 . However, the specific rotation of the synthetic compound was opposite to that reported for natural amphirionin-4. , Considering the extreme proliferation-promoting activity of (+)-amphirionin-4 in ST-2 cells, its structural features, and its potential medicinal application, we sought to develop a convergent and concise enantioselective synthesis of (+)-amphirionin-4.…”
mentioning
confidence: 99%